2015
DOI: 10.1038/nchembio.1927
|View full text |Cite
|
Sign up to set email alerts
|

Notch-modifying xylosyltransferase structures support an SNi-like retaining mechanism

Abstract: A major remaining question in glycobiology is how a glycosyltransferase (GT) that retains the anomeric linkage of a sugar catalyzes the reaction. Xylosideα1–3 Xylosyltransferase (XXYLT1) is a retaining GT that regulates Notch receptor activation by adding xylose to the Notch extracellular domain. Here, using natural acceptor and donor substrates and active Mus musculus XXYLT1, we report a series of crystallographic snapshots along the reaction, including an unprecedented natural and competent Michaelis reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 46 publications
2
90
2
Order By: Relevance
“…A nice example is a recent research on the tumor suppressor role of Notch pathway in bladder cancer, revealed by the characterization of multiple components of Notch pathway 100. We have recently characterized a Notch‐modifying enzyme Xxylt1 101 that is frequently amplified in specific cancer types lacking loss‐of‐function XXYLT1 mutations. Surprisingly, of the six cancer types with highest XXYLT1 amplification frequency, three are squamous cell carcinomas: SCCs of head and neck, lung, and cervical.…”
Section: Discussionmentioning
confidence: 99%
“…A nice example is a recent research on the tumor suppressor role of Notch pathway in bladder cancer, revealed by the characterization of multiple components of Notch pathway 100. We have recently characterized a Notch‐modifying enzyme Xxylt1 101 that is frequently amplified in specific cancer types lacking loss‐of‐function XXYLT1 mutations. Surprisingly, of the six cancer types with highest XXYLT1 amplification frequency, three are squamous cell carcinomas: SCCs of head and neck, lung, and cervical.…”
Section: Discussionmentioning
confidence: 99%
“…Yun et al solved X-ray structures of the endoplasmic reticulum enzyme Xyloside α-1,3-xylosyltransferase (XXYLT1), a well conserved type II membrane protein that can extend O-glucose modifications within Notch EGF repeats. In addition they solved the structure of Rumi alone and in complex with an EGF repeat derived from the coagulation factor IX containing a Xyl-Glc disaccharide modification (Yu et al, 2016; Yu et al, 2015). These structures provided mechanistic insights into how these enzymes bind to and modify Notch.…”
Section: ) Structural Biology Illuminates Receptor-ligand Interactiomentioning
confidence: 99%
“…These structures provided mechanistic insights into how these enzymes bind to and modify Notch. In the apo structure (the enzyme without a substrate), XXYLT1 forms a dimer such that the enzyme active sites are in an ideal conformation to interact with laterally oriented Notch EGF repeats within ER lumen (Yu et al, 2015). The structure of XXYLT1 is largely unchanged when in complex with the EGF repeat but unexpectedly, the structure of the EGF repeat undergoes a large conformational change while maintaining all disulfide bonds.…”
Section: ) Structural Biology Illuminates Receptor-ligand Interactiomentioning
confidence: 99%
“…In the presence of such a group, a double-displacement mechanism would ensue with the intermediacy of a covalent glycosyl-enzyme adduct [1,7]. Whereas, in the absence of such a putative nucleophile, a front-face reaction pathway has been postulated with the formation of a short-lived oxocarbenium ion-like intermediate [8][9][10][11][12] (Figure 1a). …”
Section: Introductionmentioning
confidence: 96%